GIVING BIRTH TO A NEW NATION: FEMALE MEDIATION AND THE SPREAD OF TEXTUAL KNOWLEDGE IN DRACULA. Issue 2 (5th May 2017) - Straight, Alyssa
Abstract : After his harrowing escape from Castle Dracula, Jonathan Harker entrusts his journal, and the secret of his traumatic experiences with the vampire Count contained therein, to his new wife, Mina Harker (née Murray). "Here is the book, " he urges; "Take it and keep it, read it if you will, but never let me know; unless, indeed, some solemn duty should come upon me to go back to the bitter hours, asleep or awake, sane or mad, recorded here" (Stoker 100; ch. 9). Mina clasps the book, sealing it with a kiss, as she replies, "it would be an outward and visible sign for us all our lives that we trusted each other." This scene from Bram Stoker's Dracula (1897) catalyzes the novel's concern with how knowledge transfer and technology intersect with women's bodies and labor. Not only is Mina the one trusted with the diary, but she is also the only person within the novel who has the required skills to translate its shorthand into a typed and readable document. In this solemn scene, which precedes and resembles their marriage vows, Mina both gains access to private information and is charged with deciding who else should have access to that knowledge and under what circumstances. This "trust" secures Mina as the mediator of knowledge and the curator of what will become an increasingly expansive imperial archive within the novel.